1983
DOI: 10.1111/j.1751-0813.1983.tb05925.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of α‐mannosidosis in Angus cattle

Abstract: SUMMARY Tests for the detection of animals heterozygous for a‐mannosidosis were undertaken on samples taken from 34,203 cattle registered with the Angus Society of Australia. Results indicates 1,836 (5.4%) of the animals were heterozygotes. Heterozygotes were detected in 214 (51%) of the herds examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The results of screening programmes conducted with the support of the respective breed societies indicate that prior to introduction of the programmes approximately 13% of registered Brahmans (McPhee & Reichmann 1990), 20% of registered Poll Shorthorns (Healy, unpublished observations) and 5.4% of registered Angus (Healy et al 1983) were heterozygous for the respective defect. The results of screening programmes conducted with the support of the respective breed societies indicate that prior to introduction of the programmes approximately 13% of registered Brahmans (McPhee & Reichmann 1990), 20% of registered Poll Shorthorns (Healy, unpublished observations) and 5.4% of registered Angus (Healy et al 1983) were heterozygous for the respective defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of screening programmes conducted with the support of the respective breed societies indicate that prior to introduction of the programmes approximately 13% of registered Brahmans (McPhee & Reichmann 1990), 20% of registered Poll Shorthorns (Healy, unpublished observations) and 5.4% of registered Angus (Healy et al 1983) were heterozygous for the respective defect. The results of screening programmes conducted with the support of the respective breed societies indicate that prior to introduction of the programmes approximately 13% of registered Brahmans (McPhee & Reichmann 1990), 20% of registered Poll Shorthorns (Healy, unpublished observations) and 5.4% of registered Angus (Healy et al 1983) were heterozygous for the respective defect.…”
Section: Discussionmentioning
confidence: 99%
“…respectively. In contrast, the relative efficiency of tests for detection of heterozygotes for a-mannosidosis was found to be high, with the most frequent complication being faulty breeding records (Jolly et al 1974;Healy et al 1983). The prevalence of heterozygotes for these two defects has been reduced by utilization of heterozygote detection tests that exploit reduced activities of the respective enzymes in peripheral leucocytes of heterozygotes (Healy 1981(Healy ,1982a.…”
mentioning
confidence: 90%
“…Knowledge of the prevalence of twinning and of heterozygotes for specific defects is necessary in order to assess the likely impact of incorrect diagnoses, caused by haemopoietic chimaerism, upon disease control programmes. The results of screening programmes conducted with the support of the respective breed societies indicate that prior to introduction of the programmes approximately 13% of registered Brahmans (McPhee & Reichmann 1990), 20% of registered Poll Shorthorns (Healy, unpublished observations) and 5.4% of registered Angus (Healy et al 1983) were heterozygous for the respective defect. The prevalence of natural twinning in Australian beef cattle is probably similar to the 1% reported in North American (Rutledge 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of routine tests for detection of Brahmans heterozygous for generalized glycogenosis, McPhee Correspondence: P J Healy. Accepted 26 August 1993 and Reichmann (1990) concluded that the efficiency of the test was compromised by environmental factors and possibly confounded by additional genetic factors. In contrast, the relative efficiency of tests for detection of heterozygotes for a-mannosidosis was found to be high, with the most frequent complication being faulty breeding records (Jolly et al 1974;Healy et al 1983). Definition of mutations responsible for citrullinaemia and bovine leucocyte adhesion deficiency led to the development of DNA-based tests for detection of heterozygotes (Dennis et al 1989;Shuster et al 1992).…”
mentioning
confidence: 90%
“…The majority of the affected calves are stillborn or fail to survive the immediate postnatal period. The animals that survive show severe and progressive neurological disease characterized by tremors of the head, ataxia and aggression (71)(72).…”
Section: Animal Modelsmentioning
confidence: 99%